Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Sure! Let's tackle this question step by step.
### Monomial by Constant Term
We will multiply each monomial by the given constant term:
1. \( 4(y) = 4y \)
2. (ab) \( 2 = (ab) \cdot 2 = 2ab \)
3. \( 3(3 b') = 3 \cdot 3b' = 9b' \)
4. \( 12(y^2) = 12y^2 \)
5. \( (x^2 y) \cdot 5 = x^2 y \cdot 5 = 5x^2 y \)
6. (ab) \( \frac{1}{8} = ab \cdot \frac{1}{8} = \frac{ab}{8} \)
### Monomial by Monomial
Now, we multiply each pair of monomials:
1. \( 2a = 2a \)
2. \( x(10x) = x \cdot 10x = 10x^2 \)
3. \( 2a(4a) = 2a \cdot 4a = 8a^2 \)
4. \( y(8y) = y \cdot 8y = 8y^2 \)
5. \( a(8b) = a \cdot 8b = 8ab \)
6. \( ab(2b) = ab \cdot 2b = 2ab^2 \)
7. \( 4b(8bc) = 4b \cdot 8bc = 32b^2c \)
8. \( 3x(x y) = 3x \cdot xy = 3x^2y \)
9. \( 9a(4ab) = 9a \cdot 4ab = 36a^2b \)
10. \( (8b) \cdot 9 = 8b \cdot 9 = 72b \)
11. \( 4(2x) = 4 \cdot 2x = 8x \)
12. \( -3(8x) = -3 \cdot 8x = -24x \)
### Monomial by Binomial
Finally, we will distribute each monomial across the terms of the binomial:
1. \( x(5x - 4) = x \cdot 5x - x \cdot 4 = 5x^2 - 4x \)
2. \( 2x(8x - 3x) = 2x \cdot 8x - 2x \cdot 3x = 16x^2 - 6x^2 = 10x^2 \)
3. \( (6b \div b) \cdot 7b = 6 \cdot 7b = 42b \)
4. \( 4b(a - 2b) = 4b \cdot a - 4b \cdot 2b = 4ab - 8b^2 \)
5. \( 62 \left( \frac{2x}{3} \right) = 62 \cdot \frac{2x}{3} = \frac{124x}{3} \)
6. \( (3b - 2a) \cdot 5ab = 3b \cdot 5ab - 2a \cdot 5ab = 15ab^2 - 10a^2b \)
7. \( (5b + 2) \cdot 7b = 5b \cdot 7b + 2 \cdot 7b = 35b^2 + 14b \)
8. \( x \left( \frac{8x}{9y} \right) = x \cdot \frac{8x}{9y} = \frac{8x^2}{9y} \)
9. \( a(3a + 4) = a \cdot 3a + a \cdot 4 = 3a^2 + 4a \)
This completes the detailed step-by-step solution for the given problem.
### Monomial by Constant Term
We will multiply each monomial by the given constant term:
1. \( 4(y) = 4y \)
2. (ab) \( 2 = (ab) \cdot 2 = 2ab \)
3. \( 3(3 b') = 3 \cdot 3b' = 9b' \)
4. \( 12(y^2) = 12y^2 \)
5. \( (x^2 y) \cdot 5 = x^2 y \cdot 5 = 5x^2 y \)
6. (ab) \( \frac{1}{8} = ab \cdot \frac{1}{8} = \frac{ab}{8} \)
### Monomial by Monomial
Now, we multiply each pair of monomials:
1. \( 2a = 2a \)
2. \( x(10x) = x \cdot 10x = 10x^2 \)
3. \( 2a(4a) = 2a \cdot 4a = 8a^2 \)
4. \( y(8y) = y \cdot 8y = 8y^2 \)
5. \( a(8b) = a \cdot 8b = 8ab \)
6. \( ab(2b) = ab \cdot 2b = 2ab^2 \)
7. \( 4b(8bc) = 4b \cdot 8bc = 32b^2c \)
8. \( 3x(x y) = 3x \cdot xy = 3x^2y \)
9. \( 9a(4ab) = 9a \cdot 4ab = 36a^2b \)
10. \( (8b) \cdot 9 = 8b \cdot 9 = 72b \)
11. \( 4(2x) = 4 \cdot 2x = 8x \)
12. \( -3(8x) = -3 \cdot 8x = -24x \)
### Monomial by Binomial
Finally, we will distribute each monomial across the terms of the binomial:
1. \( x(5x - 4) = x \cdot 5x - x \cdot 4 = 5x^2 - 4x \)
2. \( 2x(8x - 3x) = 2x \cdot 8x - 2x \cdot 3x = 16x^2 - 6x^2 = 10x^2 \)
3. \( (6b \div b) \cdot 7b = 6 \cdot 7b = 42b \)
4. \( 4b(a - 2b) = 4b \cdot a - 4b \cdot 2b = 4ab - 8b^2 \)
5. \( 62 \left( \frac{2x}{3} \right) = 62 \cdot \frac{2x}{3} = \frac{124x}{3} \)
6. \( (3b - 2a) \cdot 5ab = 3b \cdot 5ab - 2a \cdot 5ab = 15ab^2 - 10a^2b \)
7. \( (5b + 2) \cdot 7b = 5b \cdot 7b + 2 \cdot 7b = 35b^2 + 14b \)
8. \( x \left( \frac{8x}{9y} \right) = x \cdot \frac{8x}{9y} = \frac{8x^2}{9y} \)
9. \( a(3a + 4) = a \cdot 3a + a \cdot 4 = 3a^2 + 4a \)
This completes the detailed step-by-step solution for the given problem.
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.